1991
DOI: 10.1103/physrevlett.67.1177
|View full text |Cite
|
Sign up to set email alerts
|

Resonant soliton-impurity interactions

Abstract: We describe a new type of soliton-impurity interaction and demonstrate that the soliton can be totally reflected by an attractive impurity if its initial velocity lies in certain resonance "windows." This effect has an analogy with the resonance phenomena in kink-antikink collisions [Campbell, Schonfeld, and Wingate, Physica (Amsterdam) 9D, 1 (1983)], and it can be explained by a resonant energy exchange between the soliton and the impurity mode. Taking the sine-Gordon and 0"^ models as examples, we find a num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
0
9

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(141 citation statements)
references
References 12 publications
6
126
0
9
Order By: Relevance
“…The effects of medium disorders and impurities can be added to the equation of motion as perturbative terms [7,8]. These effects also can be taken into account by making some parameters of the equation of motion to be function of space or time [9,10].…”
Section: Soliton-potential Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of medium disorders and impurities can be added to the equation of motion as perturbative terms [7,8]. These effects also can be taken into account by making some parameters of the equation of motion to be function of space or time [9,10].…”
Section: Soliton-potential Systemmentioning
confidence: 99%
“…For this situation equations (4) reduce to [6] ∂∂φ 0 = λsinφ 0 ∂∂φ 1 = λφ 1 cosφ 0 (7) and the constraint equation…”
Section: Noncommutative Sine-gordon Modelmentioning
confidence: 99%
“…Solitons are now generated in nonlinear transmission lines, optical fibers (bright and dark solitons), Josephson junctions, crystals, etc. [1] Almost a decade ago Kivshar et al [2] noted that a soliton interacting with an impurity modelled as an external potential or a space dependent mass term, generates a wealth of phenomena ranging from repulsion by an attractive impurity and trapping of a positive kinetic energy soliton in an attractive well. The mechanism of trapping consists in a soliton arriving at the site of an attractive potential and oscillating inside it for an infinite time without the possiblity of reemerging from it.…”
Section: Decay Of a Soliton In A Wellmentioning
confidence: 99%
“…Trapping can be understood in terms of a few degrees of freedom for the soliton [2], namely, the center of the soliton, a shape mode excitation and an impurity mode. [6] These characteristics of soliton scattering from an attractive well are generic and apply also to Sine-Gordon solitons and perhaps even other solitons, not researched until now.…”
Section: Decay Of a Soliton In A Wellmentioning
confidence: 99%
“…In the last few decades it has been demonstrated that di erent kinds of perturbations give rise to many interesting phenomena (see e.g., Refs. [4,5] and references therein). For the nonintegrable systems various resonance e ects may take place [5±11].…”
Section: Introductionmentioning
confidence: 99%